Evaluasi Kualitas Bahan Pakan Alternatif untuk Unggas Berbahan Dasar Maggot: Evaluation of Alternative Feed Ingredients for Poultry Based on Maggot - Nurkholidza, W; Dewi, Sari Putri; Rayani, T F; Sembada, P; Ayuningtyas, G; Priyambodo, D; Kurniawan, F A (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
The increasing cost of fish meal has become a concern for farmers. An alternative replacement is Black Soldier Fly (BSF) maggot meal. The research aims to assess the nutritional quality and physical properties of BSF maggot meal as a replacement for fishmeal. The analyses included proximate analysis and fatty acid profile analysis. The research design used a Completely Randomized Design (CRD) with different living media, namely P0 = 100% kitchen organic waste, P1 = 50% kitchen organic waste and 50% cow manure, and P2 = 50% kitchen organic waste and 50% cow milk waste, along with different milling methods, namely defatted and full fat. The results showed that samples with a mixed substrate of 50% kitchen organic waste and 50% cow milk waste, using the defatted milling method, showed high protein content. Samples with a substrate mix of 50% kitchen organic waste and 50% cow feces, using the full-fat milling method, demonstrated the best balance of saturated and unsaturated fats. It can be concluded that each treatment presented different nutritional advantages, suggesting that BSF maggot meal has strong potential as an alternative animal protein source in poultry feed. Key words: alternative feed, cultivation media, maggots, nutritional content, animal protein